The Toxicity Assessment of Hydroxyapatite with Theobromine Formulation on Human Dental Pulp Stem Cells (hDPSC) - Clara Pricilla Suarthana; Elline Elline; Anastasia Elsa Prahasti; Aryadi Aryadi (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2025)
Background: Deep caries not treated immediately can cause more severe damage and loss of tooth vitality. Ca(OH)2 and MTA are often used as vital pulp treatment materials, but both have limitations. Therefore, alternative materials are needed. Hydroxyapatite is a major component of bones and teeth forms reparative dentin without tunnel defects, while theobromine has been shown to have a better anti-cariogenic effect than fluoride. The combination of both can be a choice for vital pulp treatment. Therefore, conducting cytotoxicity and cell proliferation tests is important to ensure safety and determine whether the material can induce cell proliferation. Objective: To determine the toxicity and proliferation of hydroxyapatite theobromine on human dental pulp stem cells. Materials and Methods: The toxicity assessment of hydroxyapatite with theobromine formulation on human dental pulp stem cells (hDPSC) was a laboratory experimental study (in vitro) carried out using a posttest control group design with the method used being the MTT assay. Results: The highest cell viability value was Ca(OH)2 122.08%, control cells 113.70%, HA/TB 2:1 108.03%, HA/TB 1:1 103.23%, HA/TB 1:2 102.09%, and the lowest was negative control 100%. The highest proliferation value was in control cells 138.00%, HA/TB 2:1 135.00%, HA/TB 1:2 129.64%, Ca(OH)2 128.38%, and HA/TB 1:1 122.11%, and the lowest cell proliferation value was in the negative control at 100%. This shows that the higher the hydroxyapatite value compared to theobromine, the greater the percentage value. Conclusion: Theobromine hydroxyapatite formulation is non-toxic, so it has potential as a vital pulp treatment ingredient, but it is less effective in inducing cell proliferation.